Relationship between psychological resilience and stress coping strategies in karate athletes (Revista de Artes Marciales Asiáticas, 2020)
The aim of this research was to examine the psychological resilience and stress coping strategies of Karate athletes according to some demographic variables and to determine the relationship between them. A sample of 104 (54 females and 50 males, mean age 19.85±4.10 years) Karate athletes who trained in different sport clubs in Turkey were recruited. The Brief Resilience Scale (BRS) (Smith et al., 2008) and the Stress Coping Scale (SCS) (Sahin & Durak, 1995) were used for data collection. Descriptive statistics, t-test and correlation analyses were used for data analysis. Participants’ psychological resilience was at mid-level, while the SCS self-confident approach and seeking social support sub-dimensions were at high and low level respectively. The athletes’ psychological resilience and stress coping strategies differed significantly according to gender. There was a positive and low significant correlation between experience and psychological resilience, in contrast a to negative and low significant correlation found between experience and helpless approach SCS sub-dimension. Middle and positive correlation was observed between age and psychological resilience. Finally, there were positive and middle significant correlations between psychological resilience and self-confident approach and optimistic approach, and a negative and middle significant correlation between psychological resilience and helpless approach SCS sub-dimensions.